2016
DOI: 10.2967/jnumed.116.177030
|View full text |Cite
|
Sign up to set email alerts
|

A Preanalytic Validation Study of Automated Bone Scan Index: Effect on Accuracy and Reproducibility Due to the Procedural Variabilities in Bone Scan Image Acquisition

Abstract: The effect of the procedural variability in image acquisition on the quantitative assessment of bone scan is unknown. Here, we have developed and performed preanalytical studies to assess the impact of the variability in scanning speed and in vendor-specific γ-camera on reproducibility and accuracy of the automated bone scan index (BSI). Methods: Two separate preanalytical studies were performed: a patient study and a simulation study. In the patient study, to evaluate the effect on BSI reproducibility, repeat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
23
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 14 publications
0
23
0
Order By: Relevance
“…It is believed that machine learning will change radiology and nuclear medicine in the future (5). There have been recent publications on the use of machine learning algorithms for classification and segmentation purposes (6)(7)(8)(9)(10). CNNs have been used to obtain standard-dose CT and PET images from low-dose data (11,12) and to enhance images by determining scatter correction parameters (13) and CNN-augmented emission-based attenuation correction (14) in PET.…”
mentioning
confidence: 99%
“…It is believed that machine learning will change radiology and nuclear medicine in the future (5). There have been recent publications on the use of machine learning algorithms for classification and segmentation purposes (6)(7)(8)(9)(10). CNNs have been used to obtain standard-dose CT and PET images from low-dose data (11,12) and to enhance images by determining scatter correction parameters (13) and CNN-augmented emission-based attenuation correction (14) in PET.…”
mentioning
confidence: 99%
“…The effect of variability in image acquisition on the BSI calculation was analyzed during the pre-analytical validation. 30 The results showed that the BSI is dependent on the quality of anterior and posterior images defined as counts, but not on vendor-specific gamma cameras. It is therefore recommended that the scan speed be adjusted to ensure that the total count is ≥1.5 million per image; that is, to adhere to the guidelines of the Society of Nuclear Medicine and Molecular Imaging.…”
Section: European and North American Perspectivesmentioning
confidence: 89%
“…The effect of variability in image acquisition on the BSI calculation was analyzed during the pre‐analytical validation . The results showed that the BSI is dependent on the quality of anterior and posterior images defined as counts, but not on vendor‐specific gamma cameras.…”
Section: European and North American Perspectivesmentioning
confidence: 99%
“…Automated Bone Scan Index (aBSI) is suggested to act as an imaging biomarker of whole-body bone-metastatic burden, and it represents the percentage of the total skeletal mass affected by metastases [4,5]. The aBSI is software developed using artificial intelligence for calculation from images acquired in whole-body bone scintigraphy within a few seconds, and it has been validated preanalytically and analytically as an imaging biomarker in patients with metastatic PCa [6,7].…”
Section: Introductionmentioning
confidence: 99%